Using Instructional Materials to Develop Higher Order Thinking Skills - Kunasunthary Duraippah,; Zahari Hamidon,; Ong, Peter (ASEAN Journal of Open and Distance Learning, 2021)
This paper investigates and explores the use of instructional materials for a learning environment to develop higher order thinking skills. This study was conducted in an international school in Kuala Lumpur. This research is based on qualitative research involving unstructured interviews to obtain more complex or personal information. A total of three participants were voluntarily selected for this interview; the principal, the Information Communication and Technology teacher and one student from Year 10 were involved in this research. More participants could not be interviewed due to the second phase of the Covid-19 pandemic. Information Communication and Technology is used to improve students’ learning performance including higher order thinking skills to enable students to ask logical and intelligent questions and to help students solve solutions to understand the target knowledge. Instructional materials used in Information Communication and Technology lessons during teaching and learning exercise to engage more effectively with the learners. Tools used include digital worksheets, quizzes, and assignments. The findings of this study show that this research school inspires teachers to create instructional materials and incorporate higher order thinking skills into the daily teaching and learning. higher order thinking skills are elements that incorporate creativity skills, communication skills, collaboration skills and critical thinking skills. The right pedagogy and development higher order thinking skills together can develop a culture of thinking and facilitate students to develop advanced ideas and imagination, while enhancing students’ abilities to analyse and evaluate information by working collaboratively to create new knowledge and solutions. The Information Communication and (Abstract by authors)